Human behavior and the social environment : shifting paradigms in essential knowledge for social work practice - Schriver, Joe M. (Connecting core competencies series, 2011)
Human Behavior and the Social Environment: Shifting Paradigms in Essential Knowledge for Social Work Practice explores, compares, and contrasts both traditional and alternative paradigms in examining human behavior and the social environment.